Do adolescents accurately evaluate their diet quality? The HELENA study. Issue 6 (December 2017) - Vanhelst, Jérémy; Béghin, Laurent; Duhamel, Alain; De Henauw, Stefaan; Ruiz, Jonatan R.; Kafatos, Anthony; Androutsos, Odysseas; Widhalm, Kurt; Mauro, Beatrice; Sjöström, Michael; Kersting, Mathilde; Gottrand, Frédéric
Summary: Background & aims: The aim of this study was to assess the diet quality awareness and associated factors in a large sample of European adolescents. Methods: The study included 3389 healthy adolescents, aged 12.5–17.5 years, who participated in the Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA) Study. The adolescents' diet quality was based on repeated 24 h recalls and scored into a Diet Quality Index for Adolescents (DQI-A) considering four components: meal, equilibrium, diversity and quality. A self-rated diet quality questionnaire was administered to adolescents to assess their dietary awareness. The association of DQI-A with dietary awareness was studied using a linear mixed model including the center as the random effect and dietary awareness as the fixed effect. Results: There was a positive association between DQI-A scores and diet quality perception levels ( p < 0.0001). The mean DQI-A was 59.0 (SD = 14.8) in adolescents with a low dietary awareness compared with 65.4 (SD = 12.6) in adolescents with high dietary awareness ( p < 0.0001). Similar results were found for all the DQI components. When analyses were stratified, we found a significant heterogeneity across the nutritional status, with no significant association between DQI-A and dietary awareness level in obese adolescents, but a positive association in overweight, normal and undernourished groups. We found also a significant heterogeneity associated with the lunch location (school or home). No other factor affected dietary awareness (gender, pubertal status and maternal educational level). Conclusion: European adolescents evaluate well their food quality whatever their pubertal status, gender and parental educational level, except for the obese who are not able to assess their diet quality. Improving the dietary awareness in obese adolescents might help to induce behavioral changes.